1998
DOI: 10.1055/s-2006-957422
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Petasin and Pyrrolizidine Alkaloids in Leaves and Rhizomes ofin situGrownPetasites hybridusPlants

Abstract: Various locations in Switzerland were screened for Petasites hybridus plants with high petasin and low pyrrolizidine alkaloid content. The mean petasin content of the various populations ranged from 7.4 to 15.3 mg/g dry weight in rhizomes and from 3.3 to 11.4 mg/g dry weight in leaves. Mean pyrrolizidine alkaloid content in rhizomes ranged from 5 to 90 ppm whereas leaves contained between 0.02 to 1.50 ppm. These results suggest that leaves might be a preferable source for harvesting compared to the underground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 3 publications
2
27
0
Order By: Relevance
“…Th e lowest amount of total PAs was found in Petasites hybridus extract (59.61 ± 0.22 μg/g dry mass). Th e results of the spectrophotometric assay are consistent with the ones found in the literature [5,12,13].…”
Section: Discussionsupporting
confidence: 90%
“…Th e lowest amount of total PAs was found in Petasites hybridus extract (59.61 ± 0.22 μg/g dry mass). Th e results of the spectrophotometric assay are consistent with the ones found in the literature [5,12,13].…”
Section: Discussionsupporting
confidence: 90%
“…These literatures [19] and our results provide useful analysis method for determination of bekkenolide B. Wildi et al [20] conducted the analyses of petasin distribution in rhizomes and leaves of the plant. The mean petasin content of populations ranged from 7.4 to 15.3 mg/g dry weight in rhizomes and from 3.3 to 11.4 mg/g dry weight in leaves of P. hybridus.…”
Section: Structure Elucidation Of Bakkenolide Bmentioning
confidence: 56%
“…4) and petasin rich extracts [8,20] since the changes in petasin concentrations between leaves and rhizomes of the plant are not tremendous [3]. …”
Section: Structure Elucidation Of Bakkenolide Bmentioning
confidence: 99%
“…17) Among these, the retronecine type, including senecionine and integerrmine, are reported to be major pyrrolizidine alkaloids in butterbur species, 33,34) although at low levels. 19) Pyrrolizidine alkaloids usually do not have toxic effects per se, but the formation of reactive pyrrolic ester metabolites catalyzed by cytochrome P-450 monooxygenase is primarily responsible for hepatotoxicity and carcinogenicity in experimental animals. 13) Despite similar structures, it has been observed that differing CYP modulation is dependent on the type of pyrrolizidine alkaloid present.…”
Section: Discussionmentioning
confidence: 99%
“…17) Hence, some researchers have suggested that unpurified butterbur or extracts can be hepatotoxic and carcinogenic in livestock. 9,16,18) Recently, Wildi and colleagues 19) suggested that the leaves of P. hybridus contain a negligible level of toxicants and are clearly a good source for drug. To date, however, there have been few reports on evaluation of the safety of Japanese butterbur leaves.…”
mentioning
confidence: 99%